Influence of alcohol-containing mouthwash and alcohol-free mouthwash towards the hybrid composite restoration materials surface hardness - Munawar, Adlina Hasna; Febrida, Renny; Nurdin, Denny (Universitas Padjadjaran, 2013)
Mouthwash is widely used by the community to maintain oral health. Beside the benefit provided, both alcohol-containing mouthwash and alcohol-free mouthwash have negative effects on the composite resin restorative materials, which can affect the surface hardness. One of composite types is hybrid type which is superior in physical and mechanical properties as a restorative material. The aim of this study was to determined the effect of alcohol-containing mouthwash and alcohol-free mouthwash towards the surface hardness of hybrid composite restorative material. This study used 15 disc-shaped specimens of hybrid composite with the size of 6 mm diameter and 4 mm thickness and divided into three treatment groups immersion, in the alcohol-containing mouthwash (A), alcohol-free mouthwash (B), and artificial saliva (C) as control for 12 hours, which surface hardness was further tested using Vickers hardness test. The mean of hardness values of group: A 24.9 VHN; B: 27.2 VHN; and C: 28.4 VHN. The results of statistical tests One-Way ANOVA showed there were significant differences in the hardness values among the three treatment groups (p<0,05). From this study concluded that both alcohol-containing mouthwash and alcohol-free mouthwash were decreasing the surface hardness of hybrid composite restorative material.